Solventes eutéticos à base de cloreto de colina: uso na eletrodeposição de prata e caracterização termodinâmica - Pinheiro, Daniela Mirela Lima (2021)
In the perspective of developing new electrolytic baths that are environmentally safe and can replace the current aqueous baths which requires the use of cyanide in the jewelry industry, the use of eutectic solvents (DES) in silver electrodeposition was studied. The eutectic solvents studied were choline chloride (ChCl) + glycerol (G) and choline chloride + oxalic acid (OA) in molar ratio of 1:2 and 1:1, respectively, and for each DES solutions were prepared with 0.05 molL-1 silver nitrate. The physical and chemical characterizations of the systems studied were performed by determining the density, sound velocity, viscosity and refractive index in the temperature domain between 293.15 and 343.15 K at atmospheric pressure (101.13 kPa. From these experimental data, the derived properties thermal expansivity and isentropic compressibility were calculated. The DES were also characterized by FT-IR. The electrodeposition of silver onto the gold substrate in the two DES was analyzed by cyclic voltammetry technique at temperatures of 313, 323, 333 and 343 K. Physical characterization of the deposits was performed by means of two techniques, namely, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). FT-IR analysis indicated the formation of esters in the 1ChCl:1OA. The addition of silver nitrate to the solvents provided a predominance of attractive intermolecular forces in 1ChCl:1OA, whereas for 1ChCl:2G there were dominant repulsive forces. From the refractive index data, it was possible to see that 1ChCl:1OA has larger free volumes than 1ChCl:2G. This indicates that although this system is more compact, it has a greater capacity for both thermal expansion and isentropic compressibility. The most compact structure (1ChCl:1OA) had the lowest values for the speed of sound because it has a larger free volume than 1ChCl:2G and therefore the sound wave will propagate at a slower speed since it is a mechanical wave. Silver deposits were successfully obtained in both solvents. The silver reduction process in the two eutectic solvents showed a single cathodic peak with one electron transfer. The morphology of the silver deposits showed a granular structure with coalescence of these grains in 1ChCl:1AO upon increasing temperature. In 1ChCl:2G it was found that with increasing temperature there was secondary nucleation on the silver thin film. At all temperatures analyzed the 1ChCl:2G system showed higher values of the diffusion coefficient of the silver species than 1ChCl:1AO. The hydrodynamic radius (rh) values for Ag+ species in the 1ChCl:2G medium was 18.31 Å and in the 1ChCl:1AO medium was 0.59 Â at 313 K, 1.08 Å at 323 K. The rh value for 1ChCl:2G is higher than the ionic radius of this species in crystals; this suggests that the dissolved metal ions are complexed in solution. In view of all the above, DES 1ChCl:2G showed better results for electrodeposition and a more stable physicochemical characterization.